Promoting gender equality in rural climate services - Gumucio, Tatiana (International Research Institute for Climate and Society, 2019)
Presented by Tatiana Gumucio (International Research Institute for Climate and Society [IRI]) on January 23, 2019 as part of the webinar 'Guidelines and good practices for achieving gender equality outcomes through climate services'. The webinar was co-organized by the CGIAR Collaborative Platform for Gender Research and the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS).